2016
DOI: 10.1590/1984-70332016v16n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Tetraploidization in citrus rootstocks: effect of genetic constitution and environment in chromosome duplication

Abstract: -The objective of this study was to identify polyploid plants from citrus rootstocks and to evaluate the influence of the 67%) tetraploids, respectively. Differences in the number of tetraploid plants among genotypes and locations were observed in field progenies of 'C 37' (2.12%) and 'C 13' (2.04%) and in greenhouse progenies of 'C 13' (15.52%) and 'C 37' (6%). The frequency of autotetraploidization events in citrus rootstocks is common and appears to be associated to genetic constitution and environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Cytogenetically speaking, this naturally occurring tetraploid blood orange plant arose from the duplication of chromosomes in nucellar cells and the lack of division during mitosis. This would be a scenario analogous to previous findings that those “spontaneous tetraploids” with identical molecular profiles to their respective diploid parent plants are the results of duplication of the chromosome set of nucellar cells (Aleza et al, 2011; Hussain et al, 2012; Guerra et al, 2016). Furthermore, it is intriguing that the size of the homologous chromosome pairs were not always identical, such as chromosome pair 2 (Figure 3 and Supplementary Figures S1, S2).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cytogenetically speaking, this naturally occurring tetraploid blood orange plant arose from the duplication of chromosomes in nucellar cells and the lack of division during mitosis. This would be a scenario analogous to previous findings that those “spontaneous tetraploids” with identical molecular profiles to their respective diploid parent plants are the results of duplication of the chromosome set of nucellar cells (Aleza et al, 2011; Hussain et al, 2012; Guerra et al, 2016). Furthermore, it is intriguing that the size of the homologous chromosome pairs were not always identical, such as chromosome pair 2 (Figure 3 and Supplementary Figures S1, S2).…”
Section: Discussionsupporting
confidence: 73%
“…The variable frequency of spontaneous polyploid citrus plants relying on genetic and environmental control can be seen in the paper by Hussain (Hussain et al, 2012). In a similar investigation, Guerra et al (2016) showed that the frequency of autotetraploidization events in citrus rootstocks is common, and his work has shed light on the tetraploidization events in relation to genetic constitution and environmental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The cities in the state of Rio Grande do Sul where the accessions were collected and their identification in the paper are: Venâncio Aires (1); Porto Alegre (2); Gravataí (3); Gravataí (4); Cachoeirinha (5); Porto Alegre (6); Porto Alegre (7); Porto Alegre (8); Santa Cruz do Sul (9); Charqueadas (10); Eldorado do Sul (11) Young leaves were collected for DNA extraction and genetic diversity evaluation through the protocol proposed by Ferreira and Grattapaglia (1998). The quantity and quality of DNA were evaluated by applying the samples to 1% agarose gel, which was stained with ethidium bromide (0.5 ng mL ) and submitted to electrophoresis for an hour at 110 V. The quantification was performed by comparison with λ50, λ100, λ200 and λ500 Lambdas standards and the DNA quality was evaluated by the absence of DNA traces (Guerra et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…To take advantage of the improved adaptation to stress by polyploid citrus, several teams have been developing tetraploid rootstock [26][27][28][29][30][31][32][33][34]. Tetraploid rootstocks resulting from spontaneous chromosome doubling of nucellar cells in apomictic lines have been selected in parental diploid rootstock seedlings [35].…”
Section: Introductionmentioning
confidence: 99%